2011
DOI: 10.1111/j.1759-3441.2011.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Did the Global Financial Crisis Have any Impact on Economics Degree Enrolments?*

Abstract: The Great Depression is famous for enticing a whole generation of young men and women into studying economics especially in Britain and America and even in this country. What then of the great financial turbulence caused by the subprime crisis? Did it provoke an increase in student interest in economics? Or perhaps the relatively milder traverse Australia has enjoyed over the past three years has meant that student interest was not ignited by what was happening overseas. This paper scrutinises the latest enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Conversely, it may be the case that we should have expected a pick-up in student numbers, as apparently occurred in some other countries, as a result of the GFC. Millmow and Tuck (2011) indicate that the latter did not happen. Perhaps of greater importance is the negative way that economics is often portrayed in the media.…”
Section: Some Self-inflicted Woundsmentioning
confidence: 99%
“…Conversely, it may be the case that we should have expected a pick-up in student numbers, as apparently occurred in some other countries, as a result of the GFC. Millmow and Tuck (2011) indicate that the latter did not happen. Perhaps of greater importance is the negative way that economics is often portrayed in the media.…”
Section: Some Self-inflicted Woundsmentioning
confidence: 99%
“…However, it is not a wholly isolated example. This increase outperforms the national 21.3 per cent increase in all undergraduate enrolments in economics that Millmow and Tuck (2011) document for the period 2005 In addition, a study that the author conducted of social science students at La Trobe University in November 2012 found that, of the 156 students who participated in an online survey, over half (52.3 per cent) indicated that economics was a subject they wished they knew more about, with 83 per cent clearly indicating that they were more likely to enrol in subjects in economics if they were taught from a social science (political economy) perspective from within a social sciences faculty. Argyrous found that most of these units were taught outside economics departments and faculties of business.…”
Section: The Teaching Of Economics Outside Of Traditional Centresmentioning
confidence: 78%
“…One could expect to see renewed interest amongst students in economics in these countries, driven by a combination of curiosity and fear for the future (Freedman & Blair, ). However, because the current crisis has affected the above countries in a more painful way than Australia, Australian students’ interest has not been stimulated by what was happening overseas (Millmow & Tuck, ). Therefore, a fruitful strategy from the Australian instructors in economics could be the presentation and teaching of the consequences of the global financial crisis, based on the problems and concerns of the Australian economy.…”
Section: Discussionmentioning
confidence: 99%
“…These results are not presented here but are available upon request. way than Australia, Australian students' interest has not been stimulated by what was happening overseas (Millmow & Tuck, 2011). Therefore, a fruitful strategy from the Australian instructors in economics could be the presentation and teaching of the consequences of the global financial crisis, based on the problems and concerns of the Australian economy.…”
Section: Discussionmentioning
confidence: 99%